Opinions on the impact of studying/working remotely on vision impairment and the use of eye hygiene principles - Sowa, Magdalena; Pulnik, Karolina; Jurkiewicz, Beata (Journal of Education, Health and Sport, 2022)
Introduction. The COVID-19 pandemic has forced the introduction of remote learning and working. Symptoms of digital eye fatigue are increasingly reducing the quality of life. The aim of the study was to collect opinions on the impact of studying/working remotely on vision impairment and to find out the eye hygiene methods used by the respondents. Material and methods. An original questionnaire consisting of 20 closed-ended questions was used for the study. The form was filled out by 194 people aged 18-55 years (mean: 23.15 ± 6.91 years) who were studying or working at least partially remotely. Results. Respondents working remotely were most likely to spend more than 8 hours a day in front of the computer (49.02%), those working hybrid most often marked 5-6 hours (38.04%). Less than half - 44.85% - had a subjective feeling that their eyesight had deteriorated since they started learning/working remotely, and 19.07% declared that the deterioration of their eyesight had been confirmed by an examination with a specialist. Since starting to study/work online, respondents most often complained of eye fatigue (52.58%), dry eyes (34.54%), and sore/burning eyeballs (25.78%). Among eye hygiene rules, the largest percentage declared using a matte screen (48.97%), using "night mode" on an electronic device after dark (51.55%), sleeping for 7-9 hours (45.36%), and taking a break from the screen by blinking (41.24%). Few people are familiar with and use the exercise of closing and shading their eyes (6.70%) the 20-20-20 rule (4.12%), and do not use a smartphone/computer immediately before bed (2.58%). Conclusions. Most of the respondents stated subjectively, or confirmed by a specialist, that their eyesight had deteriorated, and they associate this with learning/working remotely. The most common ocular symptom in the surveyed group was eye fatigue. There is a large deficit in the knowledge and application of eye hygiene principles that can benefit the organ of vision.